G474(P) The need for education as a primary vehicle for improving paediatric palliative care (ppc) in a small island developing state (sids): results of a qualitative exploration. (May 2019) - Morris, KA; Greaves, N; Lashley, PM
Abstract : Background: Palliative Care (PC) is a recognised component of Universal Health Coverage and the UN SDG 3. In the Caribbean, perceptions of paediatric palliative care remain unexplored. There is little research in this field in the Caribbean among Health Care Professions (HCPs). Aim: This study sought to explore the perceptions and experiences of PPC amongst HCPs providing care at the sole tertiary healthcare facility in the small island developing state of Barbados. Method: Sampling was purposive. Twelve (12) participants (6 physicians and 6 nurses) with 2–28 years of paediatric experience participated in semi-structured, individual, face-to-face interviews conducted by the researcher. The average interview time per participant was 45 min and were audiotaped, transcribed verbatim by the interviewer, and subject to thematic analysis with constant comparison via manual data management. Results: It was shown that health professionals did not reference an internationally recognised definition or construct in framing their understanding of palliative care. There was consistent framing of palliative care as a terminal and end-of-life care point. This was made without reference to pain and symptom management across the disease trajectory of patients and their families who face life-threatening illnesses. Lack of education regarding what constitutes PC, in addition to the practicalities of clinical PPC, was perceived as the primary barrier to providing appropriate evidence based care, compounded by some physical plant resource limitations. Conclusion: Whilst provision of PC is a legal and ethical obligation for SIDS in the Caribbean, provision will not be possible without urgently correcting clinical educational deficits as part of the pathway for culturally acceptable and sustainable PPC service design.